Association between atherosclerosis, hearing recovery, and hearing in the healthy ear in idiopathic sudden sensorineural hearing loss: a retrospective chart analysis - Nobuyoshi Tsuzuki; Koichiro Wasano; Naoki Oishi; Ko Hentona; Marie Shimanuki; Takanori Nishiyama; Yoshihiko Hiraga; Masafumi Ueno; Narihisa Suzuki; Seiichi Shinden; Kaoru Ogawa; Hiroyuki Ozawa (Scientific Reports, 2022)
Abstract Atherosclerosis is reported to be a risk factor for the severity of idiopathic sudden sensorineural hearing loss (ISSNHL). We evaluated the hypothesis that atherosclerosis affects the hearing thresholds of both the affected and healthy sides of ISSNHL patients. We conducted multivariate analyses on retrospectively collected data of patients with ISSNHL (N = 762) to evaluate the relationship between known factors linked to atherosclerosis and hearing thresholds on affected and healthy sides and whether these factors are prognostic for hearing recovery. Older ages, vertigo or dizziness, diabetes mellitus, and congestive heart failure were significantly related to higher hearing thresholds on the affected side. Older ages, male, and vascular disease were significantly related to higher hearing thresholds on the healthy side. Vertigo or dizziness, severe hearing loss and hearing loss at high frequencies on the affected side, higher hearing thresholds on the healthy side, regular anticoagulant medication, and delayed steroid treatment were significantly related to lack of recovery. Since several atherosclerosis-related factors are associated with higher hearing thresholds on both affected and healthy sides in ISSNHL and higher hearing thresholds on the healthy side predict poorer prognosis, diagnosis, and predicting prognosis of ISSNHL may benefit from rigorous evaluation of patients’ cardiovascular comorbidities and hearing levels on both the healthy and affected sides.